Analysis of the Dynamics among Tutors in an After-School Tutoring Program in a Homeless Shelter for Families. Issue 3 (26th May 2016) - MacGillivray, Laurie; Goode, Gretchen S.
Abstract : Researchers of after-school tutoring primarily focus on educational outcomes with little attention to the social dynamics of such programs. In our qualitative case study, we examined the nature of interactions among tutors in a tutoring program at a homeless shelter for families. Employing Bourdieu's concepts of social capital and field, we found that the dynamics between tutors were complex, with tutors jockeying for position amid contestations over the rules and organization of the tutoring sessions. The implications include the significant impact that the dynamics among tutors can have on the overall program.